Real-World Evidence of Disease Burden in Obese Patients Hospitalized With Acute Bacterial Skin and Skin-Structure Infections. Issue 6 (November 2018) - McGinnis, Emily; Ayyagari, Rajeev; Tan, Ruo-Ding; Tuttle, Edward; Cammarata, Sue; Tillotson, Glenn
Abstract : Purpose: Common causes of hospitalizations in the United States are acute bacterial skin and skin-structure infections (ABSSSIs). The objectives of this retrospective study were to characterize hospitalized ABSSSI patients including comorbidities and identify the microorganisms associated with the infection. Methods: Adults (>18 years) hospitalized with 1 or more primary ABSSSI diagnosis were selected from the Cerner Health Facts electronic medical records database between 2009 and 2013. Causative microorganisms for ABSSSI and Gram-stain type were identified from microbiology culture, including patients with methicillin-resistant Staphylococcus aureus (MRSA). Results: Of the 11, 705 patients identified, 51.8% were male, with a mean age of 55 years at admission; 49.7% were obese; and 30.9% had diabetes. More than half (56.6%) of patients had no microbiology culture results. Of the patients with an identified ABSSSI-causing pathogen, 63.9% were gram-positive, including 18.4% infected with MRSA; 11.9% were gram-negative; and 24.2% had mixed infections (gram-positive and gram-negative), including 3.6% with MRSA. After adjusting for confounding variables, a significant association was noted between obesity and 30-day ABSSSI-related readmission among males, patients younger than 65 years, and patients without MRSA. Implications: Hospitalized ABSSI patients had comorbidities, including obesity, diabetes, hypertension, and depression, which can complicate antibiotic selection. Patient characteristics and pathogen coverage must be considered in antibiotic selection in ABSSSI.